Australian beef supply chain integration: case studies of the two largest Australian supermarkets. (2015) - Jie, Ferry; Parton, Kevin; Chan, Caroline
This paper examines the supply chain integration activities pursued by the two largest Australian supermarkets, Woolworths and Coles. Case study methods were adopted to analyse their beef supply chains. The research found that vertical integration enables retailers to have direct responsibility for managing the distribution processes. Supply chain innovation practices including strategic alliances, information sharing, information quality, trust and commitment contribute to the vertical integration. This study provides one of the few analyses of Australian food supply chains. The work complements other studies in the USA and UK, and reveals a different set of best practice principles in Australia. As the lean principle has been widely adopted in the Australian red meat industry, supplier relationships have a high level of buyer dependency. Forming strategic relationship among supply chain partners is critical for containing cost and maintaining operational effectiveness in the Australian beef supply chain.